2003
DOI: 10.1139/b03-089
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variability in Commelina erecta : response to phosphorus addition

Abstract: To examine intraspecific variability, we studied the biomass production and physiological responses of clonal replicates of the widespread perennial herb Commelina erecta L. grown under different phosphorus concentrations. Five replicates per genotype collected from a small population were exposed to 0.01 or 1.0 mmol·L–1 phosphate in a hydroponic solution and grown under natural radiation. High intraspecific variability occurred for ecologically important traits such as root, leaf, and total plant biomass, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Invasive Commelina species grew faster at higher nutrient levels as reported by [12]. Although severe stunting was reported on C. diffusa by high nitrogen authors in [15,16] reported altered growth and physiological characteristics for different Commelina species clones with both nitrogen and phosphorus fertilizers. The type of plasticity exhibited by plants to changes in the amount of nutrients has been described by various authors [17,18].…”
Section: Resultsmentioning
confidence: 74%
“…Invasive Commelina species grew faster at higher nutrient levels as reported by [12]. Although severe stunting was reported on C. diffusa by high nitrogen authors in [15,16] reported altered growth and physiological characteristics for different Commelina species clones with both nitrogen and phosphorus fertilizers. The type of plasticity exhibited by plants to changes in the amount of nutrients has been described by various authors [17,18].…”
Section: Resultsmentioning
confidence: 74%
“…Phosphorous elements are considered vital for plants in metabolism, cell division, photosynthesis and other many physiological and development processes. A study by Urich et al [70] demonstrated that the roots, leaves and total plant biomass of some Commelina species responded significantly in high than low phosphorus concentration. The third significant nutrient variable was the total nitrogen (TN).…”
Section: Discussionmentioning
confidence: 99%
“…U2-tobacco mosaic virus has also been found infecting C. communis and Z. pendula. Brome mosaic virus isolates have been identified [70] infecting C. diffusa and C. communis in Fayetteveille, Arkansas, USA.…”
Section: Pests and Diseases Associated With Commelina Speciesmentioning
confidence: 99%